A Question Fisher (2008)
My name is Question Asker because I always wonder about the world and I am looking for curious children who want to solve their own questions and ask new ones. Questions make knowledge possible; they allow us to explore, learn and remain open to new adventures. For this reason, asking questions is one of the pedagogical pricniples of EAFIT Children's University,.